Gallaxery Enterprise / Yusbi Helmi Mohd Yunus ... [et al.] - Mohd Yunus, Yusbi Helmi; Roslan, Fahros Faiz; Wasli, Izzati Khairunisa; Nordin, Siti Nor Silmi; Tahrrir, Siti Robikhah (Faculty of Applied Sciences, 2006)
As a new company, Gallaxery Enterprise provides designing and printing of banners, brochures and wedding cards. Set up with a better service and quality utilizing high technology of printing as an objective of the company distinguishes our company from the other companies. The industry profile involves the target market and industrial prospect. The target markets are the event organizers, schools, companies and the public itself. While then, the industrial prospect of this business is creating an advertising platform for other parties to promote and advertise their events utilizing the printing technology. With high competency in targeting market, our vision is to manipulate printing industry in Senawang Commercial Park, thus, be the first company to provide services using high-tech in its range. Within 5 years, we are expecting to expend our business nature on publishing books as our long term mission. Our short term mission is to attract as many regular customers to deal with our company.